Hepatitis B–Related Hepatic Flare During Immune Reconstitution Syndrome After Antiretroviral Treatment Initiation in an HBV Surface Antigen–Positive Patient With HIV: Viroimmunological and Histological Characterization. (29th August 2022) - Iannetta, Marco; Crea, Angela M A; Di Lorenzo, Andrea; Campogiani, Laura; Teti, Elisabetta; Malagnino, Vincenzo; Compagno, Mirko; Coppola, Luigi; Piermatteo, Lorenzo; Palmieri, Giampiero; Cimino, Carolina; Salpini, Romina; et al.
Abstract: HIV and hepatitis B virus (HBV) coinfection is relatively common. Initiation of antiretroviral therapy (ART) in people with HIV (PWH) causes a progressive restoration of cell-mediated immune functions. In the presence of overt or occult coinfections, immune restoration might lead to immune reconstitution inflammatory syndrome (IRIS). Here, we describe the clinical, immunological, virological, and histological characterization of a case of HBV-related IRIS hepatitis in a PWH after ART initiation. A liver biopsy was performed during HBV-related IRIS hepatic flare, and liver samples were analyzed through immunohistochemistry and molecular techniques, with the assessment of intrahepatic HBV-DNA, covalently closed circular DNA, and HBV pregenomic RNA through a droplet digital polymerase chain reaction system. Immune activation and senescence were also longitudinally assessed. In this clinical case, the hepatic flare occurred 6 weeks after ART initiation with a therapeutic regimen including tenofovir alafenamide (TAF) and emtricitabine (FTC). The episode was self-limiting, characterized by hyperactivation of peripheral blood CD4+ and CD8+ T-lymphocytes, and resolved without ART discontinuation, leading to the achievement of HBsAg seroconversion (HBsAg-/HBsAb+) and HBV-DNA plasma undetectability. Notably, hyperactivation of the immune system plays a pivotal role in promoting the control of HBV replication, thus triggering the achievement of HBsAg seroconversion during treatment with TAF/FTC.